Parergodrilus heideri Reisinger, 1925 (Annelida: Polychaeta) from a holm oak wood in an extinct volcano of southern Italy - Rota, Emilia; de Nicola, Flavia; Bargagli, Roberto (Zootaxa, 2010)
A well established population of the soil-dwelling polychaete Parergodrilus heideri Reisinger, 1925 was discovered during a survey of the woodland soil fauna in the Astroni Crater (a State Nature Reserve near Naples, Italy, 50 m a.s.l., 40°50′52″N, 14°08′59″E) (Fig. 1A, B). This is the southernmost capture of this worm in Europe (Fig. 2A), although a lower latitude record (35°22′0.4″N, 127°34′52″E), the sole (so far) outside the continent, has been reported recently from Korea in this same journal (Dózsa-Farkas & Hong 2010). In Italy the species was known only from the Casentino National Park (1,120 m a.s.l.) in Tuscany and the Regional Park of Suviana and Brasimone Lakes (975 m a.s.l.) in Emilia Romagna (Rota 1997; Rota et al. 2001). Also in central Europe the species appears confined to mountain habitats (650-1,200 m a.s.l.), the lowland records being located along the northern coasts of Spain and Germany and in southern Sweden (Fig. 2A, B).